2001
DOI: 10.1042/cs1000259
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional effects of extracellular pH on tumour necrosis factor-α production in RAW 246.7 and J774 A.1 cells

Abstract: The present studies determined the effects of extracellular pH (pH(o)) on the production of tumour necrosis factor-alpha (TNF-alpha) in the macrophage-like cell lines RAW 246.7 and J774 A.1. The cells were activated with lipopolysaccharide (LPS) at pH(o) 5.5, 6.5 or 7.4. TNF-alpha gene transcription was monitored by Northern blot analysis. Synthesis of the cytokine was monitored by ELISA measurements of the TNF-alpha content of cell-conditioned media (extracellularly released TNF-alpha) and cell lysates (cytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 22 publications
6
19
2
Order By: Relevance
“…Similar to West et al [20,21], Heming et al [8], and Kopernik et al [10], we observed a decreased release of IL-6 of NR 8383 cells incubated in a CO 2 atmosphere. These in vitro data fit well with the known reduction of circulating IL-6 levels in patients following laparoscopic surgery with CO 2 pneumoperitoneum compared to open surgery or laparoscopy with laparolifting techniques and room air contamination [16], as well as results of other reports that show a suppression of the inflammatory response of peritoneal macrophages following laparoscopy.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to West et al [20,21], Heming et al [8], and Kopernik et al [10], we observed a decreased release of IL-6 of NR 8383 cells incubated in a CO 2 atmosphere. These in vitro data fit well with the known reduction of circulating IL-6 levels in patients following laparoscopic surgery with CO 2 pneumoperitoneum compared to open surgery or laparoscopy with laparolifting techniques and room air contamination [16], as well as results of other reports that show a suppression of the inflammatory response of peritoneal macrophages following laparoscopy.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, they demonstrated that the effects of CO 2 could be mimicked via pharmacological modulation of the intracellular pH and thus concluded that the decrease in intracellular pH is essential for the effects of CO 2 . In contrast to the modulation of intracellular pH, Heming et al [7,8] investigated the impact of extracellular pH (pH 0 ) on the production and secretion of TNF-a by peritoneal and alveolar macrophage cultures. They demonstrated that the reduction of extracellular pH could significantly depress the release of TNF-a and simultaneously increase the accumulation of intracellular TNF-a in stimulated alveolar macrophages.…”
Section: Introductionmentioning
confidence: 98%
“…No obvious trend with time was observed in the cytosolic TNF-α content of LPS-activated alveolar mφ at pH o 7.4 (see Figure 6). In contrast, previous studies by us [22] and others [34] found significant increases with time in the cytosolic TNF-α content of mφ-like cell lines ( J774 and RAW cells) following cell activation with LPS. The reason for this discrepancy is unclear, but cellspecific differences in the LPS-induced production of TNF-α have been documented previously [35].…”
Section: Discussioncontrasting
confidence: 80%
“…In contrast, West and co-workers [20,21] reported that acidification of LPS-activated peritoneal mφ with CO # suppressed TNF-α secretion without altering TNF-α mRNA abundance. We recently documented similar effects (specifically, a decrement in LPS-induced TNF-α secretion without a change in transcript abundance) in mφ-like cell lines ( J774 A.1 and RAW 246.7 cells) incubated in acidic culture media [22]. In still other studies, incubation of peritoneal mφ in acidic dialysis fluids has been shown to decrease both LPS-induced TNF-α transcript abundance and TNF-α secretion [23].…”
Section: Introductionmentioning
confidence: 84%
“…Recently, it has been suggested that acidic microenvironments have a considerable effect on immune cells and their function [4,5]. Acidosis has been associated with proinflammatory effects on nuclear factor-κB (NF-κB) DNA binding levels and tumor necrosis factor (TNF) synthesis in macrophages [6,7]. Kos et al [8] found that a decrease in extracellular pH affected IL-6 release in macrophage subpopulations.…”
Section: Introductionmentioning
confidence: 99%